The effects of wearing a cooling vest during the warm-up on long distance interval training - Tegeder, A. R. (2006)
Reducing body temperature before exercise is called precooling. Past research suggests that reducing body core temperature (Tc) slightly can result in improved running performance. This study evaluated the effects that warming up, while wearing a cooling vest prior to an interval workout, had on Tc, and interval time in long-distance runners. Methods: Nineteen healthy male collegiate cross-country runners were recruited for this study. Each subject warmed up and exercised under two different conditions: (a) an experimental condition in which subjects wore a Nike PreCool?? ice vest during warm-up and (b) a control condition. Subjects performed a warm-up followed by running eight 1000 m intervals separated by 90 s of rest. Heart rate (HR) and Tc were measured prior to warm-up, just prior to start of the first interval, and after each interval. Results: Tc measured directly prior to the first interval was significantly lower in the vest condition than the non-vest condition (difference = 0.37?XC; P < 0.05). This difference persisted through the end of the sixth interval. Tc rose at a faster rate in the non-vest condition, though this difference was not significant (P = 0.07). Differences in HR and interval times were found to be nonsignificant between conditions for all intervals. Conclusion: Wearing an ice vest prior to and during warm-up effectively lowers Tc during long-distance interval training.